1991
DOI: 10.1021/jm00110a015
|View full text |Cite
|
Sign up to set email alerts
|

Binding of substituted and conformationally restricted derivatives of N-(3-phenyl-n-propyl)-1-phenyl-2-aminopropane at .sigma.-receptors

Abstract: Certain benzomorphans, such as N-allylnormetazocine, are classical "sigma-opiates" that bind both at sigma and phencyclidine (PCP) binding sites with modest affinity. Recently, we identified N-substituted 2-phenylaminoethane as being the primary sigma-pharmacophore of the benzomorphans and demonstrated that 1-phenyl-2-aminopropane (2) derivatives, depending upon their terminal amine substituents, constitute a novel class of high-affinity sigma-selective agents. With this pharmacophore, it is shown in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…That is, this review is based on ligands we reported in a series of articles published over the past 15 years (e.g. Ablordeppey et al, 1991;Ablordeppey et al, 1992a;Ablordeppey et al, 1992b;Ablordeppey et al, 1993;Ablordeppey et al, 1998;Ablordeppey et al, 2000;Ablordeppey et al, 2002;El-Ashmawy et al, 1992;Glennon et al, 1991a;Glennon et al, 1991b;Glennon et al, 1991c;Glennon et al, 1994;Glennon, 2000;Glennon, and Fischer 2000;Glennon et al, 2004); these papers can be consulted for the synthesis and physicochemical properties of most of the compounds described here. Sigma-2 receptor binding data were obtained using guinea pig brain homogenates and the nonselective [ One of the first sigma ligands we reported was R(-)PPAP (5R); the structure might be viewed as an N-phenylpropyl derivative of a ring-opened benzomorphan.…”
Section: Binding Character Of σ σ σ σ σ 2 Receptor Ligandsmentioning
confidence: 99%
“…That is, this review is based on ligands we reported in a series of articles published over the past 15 years (e.g. Ablordeppey et al, 1991;Ablordeppey et al, 1992a;Ablordeppey et al, 1992b;Ablordeppey et al, 1993;Ablordeppey et al, 1998;Ablordeppey et al, 2000;Ablordeppey et al, 2002;El-Ashmawy et al, 1992;Glennon et al, 1991a;Glennon et al, 1991b;Glennon et al, 1991c;Glennon et al, 1994;Glennon, 2000;Glennon, and Fischer 2000;Glennon et al, 2004); these papers can be consulted for the synthesis and physicochemical properties of most of the compounds described here. Sigma-2 receptor binding data were obtained using guinea pig brain homogenates and the nonselective [ One of the first sigma ligands we reported was R(-)PPAP (5R); the structure might be viewed as an N-phenylpropyl derivative of a ring-opened benzomorphan.…”
Section: Binding Character Of σ σ σ σ σ 2 Receptor Ligandsmentioning
confidence: 99%
“…Appropriate aryl substituents in the phenylethylamine portion of the molecule (including fused-ring structures) or decrease of the length of side chain by one or two methylene groups reserve high affinity (σKi < 10 nM) [ 70 ]. Both secondary and tertiary amines are potent ligands; however, one of the tertiary amine substituents could not be much larger than a methyl group [ 71 ]. Moreover, the phenylpentyl moiety, not a phenylethyl moiety, of 1 -type compounds was crucial for binding at σRs.…”
Section: Structure Affinity Relationship Of Sigma Receptors Modulamentioning
confidence: 99%
“…The nonrigid substructure (R)-N-ethyl-1-phenylpropan-2-amine (32) of benzomorphan (31), still retained affinity to s receptors [77]. A flexible compound 33 with an increased number of rotatable bonds exhibited high affinity for s receptors (K i = 2.6 nM) (FiguRe 8; 31 & 32) [78]. On further SAR studies with compound 33, it was observed that a phenylpentylamine moiety was important for high affinity.…”
Section: Early Development Of Sigma Ligandsmentioning
confidence: 99%